2008
DOI: 10.1057/thr.2008.24
|View full text |Cite
|
Sign up to set email alerts
|

How Tourism Destinations Evolve: The Notion of Tourism Local Innovation System

Abstract: The analysis of tourism destinations as territorial agglomerations, that is, industrial districts and clusters, has been given attention in this journal in recent years. In these analyses, tourist companies closely situated in a territory or space are claimed to benefit from available shared resources. These papers, however, do not focus on the key role that innovation and the relationships among actors have on the evolution of tourism destinations. In trying to close this gap, we use the notions of system of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 10 publications
0
35
0
8
Order By: Relevance
“…Environments with many loosely coupled links and alliances were found to promote innovative activity, especially. Novelli et al (2006) and Prats et al (2008) analyse the tourist sector from a cluster perspective and demonstrate the usefulness of the concepts of regional innovation systems.…”
Section: Theory Of Innovation Systemsmentioning
confidence: 99%
“…Environments with many loosely coupled links and alliances were found to promote innovative activity, especially. Novelli et al (2006) and Prats et al (2008) analyse the tourist sector from a cluster perspective and demonstrate the usefulness of the concepts of regional innovation systems.…”
Section: Theory Of Innovation Systemsmentioning
confidence: 99%
“…There is a perception that a destination's competitive advantage depends on the dynamic level of its agencies, as well as on the coordination of different actors and administrations (Aguiló et al, 2005). In this line, we can find, at the Spanish level, several studies analysing knowledge transmission within tourism clusters (Alvarez & Gonzalez, 2008), the dynamics of the relationships between public and private levels (Merinero, 2008) or the role that tourism clusters play when innovating and improving their competitiveness (Alvarez & Gonzalez, 2006;Prats et al, 2008), but there has not been found any study that quantifies the benefits of the cluster effect.…”
Section: Tourism Cluster and Territory Effectmentioning
confidence: 92%
“…However, in order to provide an experience for the visitor, a destination is also about a series of interactions and inter-and intra-relationships between the place and stakeholders and between stakeholders themselves. It may exhibit a number of characteristics of industrial districts (Hjalager, 2000), territorial and social capital may be considered, or it may be considered as a Tourism Local Innovation System -TLIS (Prat, Guia and Molina, 2008).…”
Section: Introductionmentioning
confidence: 99%